2017
DOI: 10.1038/icb.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulators and their mechanisms in NLRP3 inflammasome activation and signaling

Abstract: Inflammasomes are cytosolic multiprotein complexes that cause the release of biologically active interleukin-1β. The best-characterized inflammasome is the NLRP3 (nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 or Nod-like receptor protein 3) inflammasome. The NLRP3 inflammasome forms an assembly consisting of the ASC (apoptosis-associated speck-like protein containing a C-terminal caspase recruitment domain) adaptor protein and the effector, caspase-1 (cysteine-dependent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 73 publications
0
24
0
1
Order By: Relevance
“…Activation of D1 dopamine receptors on microglia increases intracellular cAMP levels, which as mentioned inhibits the NLRP3 and promotes its degradation via ubiquitination (Yan et al, 2015). Previous reviews have detailed the intracellular proteins and mechanisms that either prevent the formation or inhibit the activity of the NLRP3 inflammasome (Kim et al, 2017). …”
Section: Priming and Activation Of The Nlrp3 Inflammasomementioning
confidence: 99%
“…Activation of D1 dopamine receptors on microglia increases intracellular cAMP levels, which as mentioned inhibits the NLRP3 and promotes its degradation via ubiquitination (Yan et al, 2015). Previous reviews have detailed the intracellular proteins and mechanisms that either prevent the formation or inhibit the activity of the NLRP3 inflammasome (Kim et al, 2017). …”
Section: Priming and Activation Of The Nlrp3 Inflammasomementioning
confidence: 99%
“…This response is driven by the assembly of an inflammasome, a multimolecular complex composed of an NLR and the adaptor protein apoptosis-associated speck-like protein (ASC), which recruits caspase-1. Caspase-1 activation in the complex leads to the proteolytic maturation of the pro-inflammatory cytokine interleukin 1β (IL-1β) and interleukin 18 (IL-18) ( 108 ). Recently, it has been shown that upon detection of mitochondrial ROS, and release of mitochondrial factors, NLRP3 relocates from the ER to the ER–mitochondria appositions, thus sensing the mitochondrial alteration and assembling the inflammasome ( 109 ).…”
Section: Fundamental Structural and Functional Roles Of The Mamsmentioning
confidence: 99%
“…Among the NLRs, NLRP3 is best known for sensing the widest array of stimuli, such as nigericin, ATP, ROS, MSU and cholesterol . When the host receives a signal stimulus, NLRP3 itself can undergo oligomerization, increasing pro‐caspase‐1 through the adapter protein ASC, which activates caspase‐1 and then leads to the cleavage of the interleukin‐1β precursor (pro‐interleukin‐1β) and the interleukin‐18 precursor (pro‐interleukin‐18), causing corresponding inflammation factor IL‐1β and IL‐18 generation, thus inducing inflammation and necrosis (pyroptosis) and participating in the inflammatory response of cell and tissue …”
Section: Introductionmentioning
confidence: 99%